2010
DOI: 10.1002/ajp.20807
|View full text |Cite
|
Sign up to set email alerts
|

Validation of multi‐detector computed tomography as a non‐invasive method for measuring ovarian volume in macaques (Macaca fascicularis)

Abstract: The purpose of this study was to validate low radiation dose, contrast-enhanced, multi-detector computed tomography (MDCT) as a non-invasive method for measuring ovarian volume in macaques. Computed tomography scans of four known-volume phantoms and nine mature female cynomolgus macaques were acquired using a previously described, low radiation dose scanning protocol, intravenous contrast enhancement, and a 32-slice MDCT scanner. Immediately following MDCT, ovaries were surgically removed and the ovarian weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…22 Helms et al 12 demonstrated in a 12-month follow-up study of the both paroxysmal and permanent AF patients, using 3-dimensional MDCT that the sensitivity of large LA volumes Ͼ135 mL for predicting the recurrence of AF was 36%, and the specificity of such volumes was 96%. In the present study, the higher diagnostic accuracy of each atrial enlargement for predicting AF recurrence was obtained by quantitative 3-dimensional measurements in combination with a computer-and navigation-aided technique (OsiriX software), [17][18][19] and the value of combined atrial volumes had the highest diagnostic accuracy. The combined LA and RA enlargements may better express more remarkable, overall structural remodeling than examination of individual atrial remodeling.…”
Section: Atrial Remodeling For Predicting After Ca Af Recurrencementioning
confidence: 54%
See 1 more Smart Citation
“…22 Helms et al 12 demonstrated in a 12-month follow-up study of the both paroxysmal and permanent AF patients, using 3-dimensional MDCT that the sensitivity of large LA volumes Ͼ135 mL for predicting the recurrence of AF was 36%, and the specificity of such volumes was 96%. In the present study, the higher diagnostic accuracy of each atrial enlargement for predicting AF recurrence was obtained by quantitative 3-dimensional measurements in combination with a computer-and navigation-aided technique (OsiriX software), [17][18][19] and the value of combined atrial volumes had the highest diagnostic accuracy. The combined LA and RA enlargements may better express more remarkable, overall structural remodeling than examination of individual atrial remodeling.…”
Section: Atrial Remodeling For Predicting After Ca Af Recurrencementioning
confidence: 54%
“…OsiriX software allows the quantitative measurement of volume from 3-dimensional MDCT data. [17][18][19] Each short-axis 0.7-mm interval CT image was examined, and the region of interest was defined on the LA and RA areas ( Figure 2). Thus, RA and LA volumes were quantitatively calculated from 3-dimensional images, using OsiriX software.…”
Section: Scan Protocol and Data Acquisition Of Mdctmentioning
confidence: 99%
“…MRI-based organ volumes were measured with the freeware imaging software OsiriX (http://www.osirix -viewer.com; Rosset et al 2004). Organ volumes were determined by outlining a region of interest (ROI) around the organ with the "pencil ROI-tool" in OsiriX on a pressure-sensitive monitor (Cintiq 21UX, Wacom) in the 2-D viewer window of OsiriX (e.g., Jones et al 2010).…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…The benefit of these experimental animals is that the physiology and anatomy are similar to the human (Stevens, 1997;Weinbauer et al, 2008), although the ovarian size of the most studied cynomolgus monkey is considerably smaller (0.258+/-0.159 cm 3 ) (Jones et al, 2010) as compared to the human. Even if a lot of procedures are introduced in the human without appropriate tests in non-human primate species, it is advisable to include these animal models in preclinical research.…”
Section: Non-human Primatesmentioning
confidence: 99%